2014
DOI: 10.1149/2.0231503jes
|View full text |Cite
|
Sign up to set email alerts
|

Sea Urchin Shaped α-MnO2/RuO2Mixed Oxides Nanostructure as Promising Electrocatalyst for Lithium–Oxygen Battery

Abstract: α-MnO 2 /RuO 2 mixed oxides in the form of sea urchin shaped nanostructures were synthesized in the weight ratio of 82:18 via a simple hydrothermal method. The synthesized α-MnO 2 /RuO 2 urchin nanostructure was constructed with several straight and radially grown nanorods, and composed of homogeneously distributed MnO 2 and RuO 2 nanoparticles. When the α-MnO 2 /RuO 2 nanostructure was applied for air cathode catalyst, it displayed superior cyclic performances of lithium air battery with stable specific capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…1,10 The crystal structure of α-MnO 2 consists of 2 × 2 tunnels formed by edge-sharing MnO 6 and corner sharing MnO 6 octahedra. 1 Owing to the tunnel size and the requirement to balance the negative charge, α-MnO 2 can accommodate positive ions in the tunnel cavities, thereby providing high feasibility for bidentate O 2 adsorption sites not only on the surface but also in the bulk material.…”
Section: Fabrication Of Mgc Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…1,10 The crystal structure of α-MnO 2 consists of 2 × 2 tunnels formed by edge-sharing MnO 6 and corner sharing MnO 6 octahedra. 1 Owing to the tunnel size and the requirement to balance the negative charge, α-MnO 2 can accommodate positive ions in the tunnel cavities, thereby providing high feasibility for bidentate O 2 adsorption sites not only on the surface but also in the bulk material.…”
Section: Fabrication Of Mgc Electrodesmentioning
confidence: 99%
“…3 Although noble metals such as Pt, Pd, Ru, Au and Ag display good catalytic activity towards the ORR and OER, their low abundance and high cost impede their scalability for practical applications. [4][5][6] In recent years, economically favorable transition metal oxide catalysts (such as MnO 2 , Co 3 O 4 , Fe 3 O 4 and their composites) 1,[6][7][8][9][10] and carbon-based materials (such as carbon black, graphene and carbon nanotubes) 3,[11][12][13] have attracted great attention as electrocatalysts for metal-air batteries. Among the transition metal oxides, MnO 2 has drawn particular attention as an electrocatalyst owing to its low cost, high abundance and excellent ORR and OER catalytic activities in alkaline media.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike previously reported buckypaper cathodes which were supported by a metal substrate/current collector, [45][46][47] no additional current collector is used, increasing the practical specific capacity. RuO 2 has been proven to be an effective catalyst in nonaqueous lithium-air batteries, 29,[48][49][50][51][52][53][54] and the cathodes with RuO 2 or RuO 2 decorated supporting materials reported in previous papers were formed through casting of a slurry mixture comprising of the catalysts and binders onto a supporter/current collector. 29,[48][49][50][52][53][54] Here, the cathode was formed by directly decorating RuO 2 nanoparticles onto the surfaces of buckypaper to enhance the catalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Although single‐component α‐MnO 2 or binary composites of α‐MnO 2 and carbon materials could show excellent activity over the course of discharge/charge, as mentioned above, a high OER overpotential remained. In order to further lower the charge potential, many efforts have been made to design more efficient α‐MnO 2 ‐based bifunctional catalysts/cathodes, such as noble metals and their oxides modified α‐MnO 2 , and other transition metal oxides modified α‐MnO 2 . On noble metals modification aspect, Pd decorated mesoporous α‐MnO 2 nanotubes (Pd@α‐MnO 2 ) enhanced the discharge specific capacity, meanwhile, the charging potential was controlled at 3.6 V .…”
Section: The Types Of Manganese‐based Oxides For Li–o2 Battery Cathodmentioning
confidence: 99%
“…Similarly, α‐MnO 2 nanorods modified with Ag particles enhanced the capacity and cycle life, but due to the excessive activity, the addition of Ag caused the decomposition of carbonate based electrolyte and formed byproduct of LiCO 3 . Jang et al reported a 3D nanostructured α‐MnO 2 /RuO 2 catalyst, and the mixed oxides with the excellent ORR activity coming from α‐MnO 2 and outstanding OER performance coming from RuO 2 apparently optimized the performance of Li–O 2 battery. Even after 50 times of stable circulation, the overpotential was only 1.2 V. On bicomponent transition metal oxides containing α‐MnO 2 aspect, Trahey et al prepared α‐MnO 2 /R‐MnO 2 (Ramsdellite) composites through concentrated sulfuric acid‐treatment of layered Li 2 MnO 3 , and the Li–O 2 battery using α‐MnO 2 /R‐MnO 2 composite bifunctional catalyst showed a high reversible capacity of 5000 mAh g −1 carbon+catalyst in propylene carbonate (PC) electrolyte solvent during early cycles.…”
Section: The Types Of Manganese‐based Oxides For Li–o2 Battery Cathodmentioning
confidence: 99%